Management Turnover and Auditor Switching: The Moderating Effect of Financial Distress - Muslim, Ahmad Bukhori; Wulandari, Dian; Alisa, Novianti; Widiastuti, Widiastuti (Jurnal Akuntansi Bisnis Pelita Bangsa, 2024)
This study examines the effect of management turnover on auditor switching, with financial distress as a moderating variable. The research employs panel least squares regression on a sample of firms, analyzing the direct and interaction effects between management turnover and financial distress. The findings reveal that management turnover has a significant positive effect on auditor switching, and this relationship is further strengthened when financial distress is present. The moderating role of financial distress highlights its importance in amplifying the likelihood of auditor switching during leadership transitions. The study concludes that organizations experiencing both management turnover and financial distress are more prone to auditor changes, underscoring the interplay between leadership dynamics and financial conditions. Limitations related to sample scope and reliance on secondary data are acknowledged, and future research is encouraged to explore broader contexts and incorporate additional variables such as corporate governance and regulatory influences.